Driving agribusiness with technology innovations - Tarnanidis, Theodore, 1977-; Vlachopoulou, Maro, 1956-; Papathanasiou, Jason (Business Science Reference, 2017)
Modern web-based applications are pertinent for businesses, as they often encourage their core competencies and capabilities. As such, the agribusiness sector must begin to take advantage of the open networks and advances in communication and information technologies in order to grow their businesses exponentially. Driving Agribusiness With Technology Innovations highlights innovative business models and theories that encourage the use of emerging technological advances to produce thriving enterprises. Featuring extensive coverage on relevant topics including digital environments, mobile agriculture, supply chain platforms, and internet marketing models, this publication is an important reference source for business managers, practitioners, professionals, and engineers who are interested in discovering emerging technology trends for agribusiness.